KONTRIBUSI MOTIVASI DAN PEMANFAATAN AKSES INTERNET SEKOLAH SEBAGAI SUMBER BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN KKPI SISWA KELAS XI MULTIMEDIA DI SMK NEGERI 2 PADANG PANJANG - Fitriani Gustina; Zulhendra Zulhendra; Ahmad Jufri (Universitas Negeri Padang, 2014)
Problems in this research that majority of students are more likely to use the Internet not to seek the information related to the subject matter , but more likely to use the Internet to play games and so on . The purpose of this study was to reveal the contribution of Motivation and Use of Internet access as a Source of Learning School Of Learning Outcomes In subjects KKPI Multimedia Class XI student at SMK Padang Panjang 2 .This research is a descriptive correlational. The population in this study a class XI student of Multimedia and sample 61 students . Sampling technique using total sampling . The technique of collecting data using questionnaires class . Then the data were analyzed using statistical methods with SPSS Version 16 for correlation and regression analysis . The results of data analysis showed : ( 1 ) Motivation accounted for 12.0 % of the student learning outcomes , ( 2 ) Internet Access Benefits School contributed 10.7 % of the student learning outcomes , ( 3 ) Motivation and Benefits of Internet access together accounted for 12.1 % of the learning outcomes.So it can be concluded that the Motivation and School Internet Access Benefits contribute to learning outcomes , the better motivation in the learning process , and the better the students' skills in the use of the internet , it will get better learning results. Keywords : Motivation , Benefits School Internet Access , Learning Outcomes